2021
DOI: 10.55563/clinexprheumatol/v1tpfo
|View full text |Cite
|
Sign up to set email alerts
|

One year in review 2021: systemic vasculitis

Abstract: Large-and small-vessel vasculitis are complex potentially life-threatening systemic autoimmune diseases that have recently been subjected to considerable immunologic and clinical research. Following the other reviews of this series, here we aim to summarise some of the most significant studies that have been recently published on the pathogenesis, clinical features and novel treatments of systemic vasculitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 32 publications
0
17
0
3
Order By: Relevance
“…However, whether to adjust glucocorticoids or immunosuppressants should be combined with other clinical characteristics and laboratory tests to evaluate disease activity and relapse tendency. Accumulating evidence suggests that AAV varies significantly according to ANCA types: PR3-AAV and MPO-AAV (6,28). PR3-ANCA positivity has previously been reported to be associated with a higher rate of disease relapse (3,29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, whether to adjust glucocorticoids or immunosuppressants should be combined with other clinical characteristics and laboratory tests to evaluate disease activity and relapse tendency. Accumulating evidence suggests that AAV varies significantly according to ANCA types: PR3-AAV and MPO-AAV (6,28). PR3-ANCA positivity has previously been reported to be associated with a higher rate of disease relapse (3,29).…”
Section: Discussionmentioning
confidence: 99%
“…A number of cohorts and long-term follow-up of clinical trials have demonstrated relapse rates that vary between 21% and 89% at 5 years, and in order to prevent disease relapse the maintenance therapy is launched after remission (4). But the optimal duration of maintenance, which is depended on the underlying ANCA serology as well as treatment, hasn't reached a consensus (5,6). While prolonged treatment with immunosuppressive drug may help reduce the incidence and severity of relapse, it also results in unnecessary treatment-related toxicity and an increased risk of adverse reactions.…”
Section: Introductionmentioning
confidence: 99%
“…The "One Year in Reviews" represent the cutting edge of this endeavour and are a unique feature of this journal. They now cover all the most relevant aspects of rheumatology (2)(3)(4)(5)(6)(7)(8)(9)(10)(11). CER was started in the era of paper journals, but over the years has gradually incorporated all the continuous revolutions of the Internet technology, yet maintaining unvaried the initial template (Fig.…”
Section: Clinical and Experimental Rheumatology Turns 40mentioning
confidence: 99%
“…According to the revised nomenclature adopted at the Chapel Hill Consensus Conference [4] , vasculitis is divided into primary (e.g., autoimmune) or secondary forms as a result of connective tissue diseases, drugs, infections, or malignancies. Clinical classification is based on vessel size allowing for the differentiation between vasculitis of large vessels (e.g., giant cell arteritis (GCA)), medium vessels (e.g., panarteritis nodosa (PAN)), and small vessels with immune complex deposits (e.g., mixed cryoglobulinemia (MC)) or antineutrophil cytoplasmatic antibodies (ANCA) (e.g., granulomatosis with polyangiitis (GPA) or microscopic polyangiitis (MPA)) [5] , [6] , [7] . However, some types may affect vessels of variable sizes, such as Behçet disease (BD) [8] .…”
Section: Introductionmentioning
confidence: 99%